Low‐noise readout circuit for thermo‐electrical cooler‐less uncooled microbolometer infrared imager. Issue 9 (4th April 2016) - Liu, Dahe; Lu, Wengao; Lei, Shuyu; Chen, Zhongjian
Abstract : A low‐noise analogue frontend readout circuit is presented for VOx microbolometer infrared imager without thermo‐electrical cooler. A modified differential mirror structure with substrate temperature and self‐heating effect compensation ability is used, targeting below 40 mK noise equivalent temperature difference (NETD) with 17 μm pixel pitch. Noise characteristics are investigated to give an optimal trade‐off approach to reach lower NETD at same power consumption compared with traditional readout structures.